Progress on Structured Biosensors for Monitoring Aflatoxin B1 From Biofilms: A Review - Qi Wang; Qingli Yang; Wei Wu (Frontiers in Microbiology, 2020)
Aspergillus exists commonly in many crops and any process of crop growth, harvest, storage, and processing can be polluted by this fungus. Once it forms a biofilm, Aspergillus can produce many toxins, such as aflatoxin B1 (AFB1), ochratoxin, zearalenone, fumonisin, and patulin. Among these toxins, AFB1 possesses the highest toxicity and is labeled as a group I carcinogen in humans and animals. Consequently, the proper control of AFB1 produced from biofilms in food and feed has long been recognized. Moreover, many biosensors have been applied to monitor AFB1 in biofilms in food. Additionally, in recent years, novel molecular recognition elements and transducer elements have been introduced for the detection of AFB1. This review presents an outline of recent progress made in the development of biosensors capable of determining AFB1 in biofilms, such as aptasensors, immunosensors, and molecularly imprinted polymer (MIP) biosensors. In addition, the current feasibility, shortcomings, and future challenges of AFB1 determination and analysis are addressed.